Fluorescent Fatty Acid Transfer from Bovine Serum Albumin to Phospholipid Vesicles: Collision or Diffusion Mediated Uptake - Bassam M Elmadhoun; Manal A Swairjo; Frank J Burczynski (Frontiers Media S.A., 2012)
Purpose: The extent of palmitate uptake by hepatocytes is dependent upon the surface charge of the extracellular binding protein. Specifically, hepatocyte uptake is greater when palmitate is bound to cationic binding proteins than when it is bound to anionic proteins. To further understand the role of protein surface charge on the uptake process of protein-bound ligands, we examined the rate of transfer of fluorescent anthroyloxy palmitic acid (AOPA) in the presence of anionic and cationic extracellular proteins to model membranes containing different surface charged groups. Method: AOPA transfer rate in the presence of bovine serum albumin (ALB; isoelectric point pI = 4.8-5.0) or modified ALB (ALBe; pI = 7.0-7.5) to negative, positive and neutral lipid vesicles was investigated using a fluorescence resonance energy transfer assay. Results: The rate of AOPA transfer from both proteins was decreased when ionic strength was increased; directly dependent on the concentration of acceptor lipid vesicles; and was affected by both the lipid membrane surface charge and protein-bound concentration. Conclusion: The data support the notion that AOPA transfer from binding proteins to lipid membranes occurred through two concomitant processes, aqueous diffusion of the unbound ligand (diffusion-mediated process) and a collisional interaction between the protein-ligand complex and acceptor membrane. The contribution of diffusional mediated transfer to the overall uptake process was determined to be 3 to 4 times less than the contribution of a collisional interaction. This study strengthened the hypothesis that charged amino acid residues on proteins are important for effective collisional interaction between protein-ligand complexes and cell membranes through which more free ligand could be supplied for the uptake process. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.